Architecture based on keyword driven testing with domain specific language for a testing system - Pereira, Ricardo B. (2020)
For Cyber-physical systems (CPSs), whose task is to test industrial products, to carry out these tests, highly qualified engineers are always needed to design the tests, since the computational part of the tests is programmed in low-level languages. To optimize this process, it is necessary to create an abstraction of current methods so that tests can be created and executed more efficiently. Although this problem has arisen within the CPS, the architecture we propose will be generic enough to solve the problem in any testing system. We intend to do this by automating some of the current processes to minimize human error. In this paper, we present a novel architecture for a testing system that abstracts single low-level programming and coding of tests, based on two main concepts: the use of Keyword Driven Testing (KDT) that will abstract tests to the person responsible for the machine; the creation of a Domain Specific Language (DSL) to help configure and design new tests without requiring the experience of a highly qualified engineer.